Answer:
52
Step-by-step explanation:
Step-by-step explanation:
The question is not well written. Let us say the function given as expressed as;
f(x) = -1/x + 3/x⁴
f'(x) means we are to differentiate the function with respect to x;
Given f(x) = axⁿ
f'(x) = naxⁿ⁻¹
f(x) = -x⁻¹ + 3x⁻⁴
Applying the differentiation formula we will have;
f'(x) = -1(-x⁻²)+(-4)3x⁻⁴⁻¹
f'(x) = x⁻²-12x⁻⁵
Express as a fraction
f'(x) = 1/x²-12/x⁵
To get f'(4), we will have to substitute x = 4 into the resulting expression
f'(4) = 1/4²-12/4(5)
f'(4) = 1/16-12/20
f'(4) = 1/16-3/5
Find the LCM
f'(4) = (5-48)/80
f'(4) = -43/80
Note that the function used was assumed but the same method can be employed to any other functions.